ANALISIS KEWENANGAN BANK TANAH TERHADAP TANAH NEGARA YANG BERIMPLIKASI DENGAN TANAH ADAT DI INDONESIA (STUDI PUTUSAN MAKAMAH KONTITUSI NOMOR: 35/PUU-X/2012) - Sepri Antoni Sitopu; Abd Harris Nasution; Mirza Nasution (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2024)
Abstract: Land is one of the natural resources listed in Article 33 of the 1945 Constitution and is implemented based on national land law in the Basic Agrarian Law. The problem in land management is the difficulty in procuring land for public interest. Much land is controlled by brokers or land speculators that are abandoned. This condition hampers national development and requires enormous funding. To overcome this, the government has formed a Land Bank which is regulated in Law Number 11 of 2020 concerning Job Creation. This study aims to describe and explain the regulation of the Land Bank in the Job Creation Law and the PP on the Land Bank Agency and the implications for national land law. Land problems in Indonesia have increased along with the presence of Law Number 11 of 2020 concerning Job Creation. The regulation of the Land Bank in the Land cluster in the law is an important topic to note because it is a crucial part of land practices. The results of the study show that the presence of the Land Bank Agency has great potential to cause overlapping authority between institutions in the land sector. Fulfillment of the value of justice is needed to create a balance of rights and obligations between the parties involved in the implementation of land banks. Fulfillment of the value of legal certainty is intended so that the state guarantees legal certainty in the form of laws and regulations that specifically regulate the implementation of land banks in Indonesia.Â Keywords: Land Bank, Agrarian Law, Utility Abstrak: Tanah merupakan salah satu sumber kekayaan alam yang dicantumkan dalam Pasal 33 UUD 1945 dan dilaksanakan berdasarkan hukum tanah nasional dalam Undang-Undang Pokok Agraria. Permasalahan dalam pengelolaan tanah adalah kesulitan melakukan pengadaan tanah bagi kepentingan umum. Banyak tanah yang dikuasai oleh makelar atau spekulan tanah yang diterlantarkan. Kondisi ini menjadikan pembangunan nasional menjadi terhambat dan memerlukan pembiayaan yang begitu besar. Untuk mengatasi hal tersebut pemerintah membentuk Bank Tanah yang diatur dalam UndangUndang Nomor 11 Tahun 2020 tentang Cipta Kerja. Penelitian ini ditujukan untuk menguraikan dan menjelaskan pengaturan Bank Tanah dalam UU Cipta Kerja dan PP Badan Bank Tanah serta implikasi yang ditimbulkan terhadap hukum tanah nasional. Permasalahan pertanahan di Indonesia menjadi bertambah seiring dengan hadirnya UndangUndang Nomor 11 Tahun 2020 Cipta Kerja. Pengaturan Bank Tanah dalam klaster Pertanahan pada undang-undang itu menjadi topik yang penting untuk diperhatikan karena merupakan bagian krusial dari praktik pertanahan. Hasil penelitian menunjukkan bahwa hadirnya Badan Bank Tanah berpotensi besar menyebabkan tumpang tindih kewenangan antar lembaga dalam bidang pertanahan. Pemenuhan terhadap nilai kepastian hukum ditujukan agar negara menjamin adanya kepastian hukum dalam wujud peraturan perundang-undangan yang secara spesifik mengatur penyelenggaraan bank tanah di Indonesia.Â Kata kunci: Bank tanah, Hukum Pertanahan, Kemanfaatan